2021
DOI: 10.1111/1471-0528.16931
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum haemorrhage trends in Sweden using the Robson ten group classification system: a population‐based cohort study

Abstract: Objective To examine postpartum haemorrhage (PPH) trends in Sweden using the Robson classification system. Design Population‐based cohort study. Setting Sweden. Population Deliveries in 2000–2016, classified as Robson groups 1–5 (singleton pregnancies in vertex presentation, from gestational weeks 37+0; n = 1 590 178). Methods We examined temporal trends in PPH between 2000 and 2016 overall, and within each Robson group, and performed logistic regression to examine the influence of changes in risk factors (mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
2
17
0
2
Order By: Relevance
“…Notably, the largest contributors to the total rates of all outcomes except CS were women with singleton term cephalic pregnancies and unscarred uterus, nulliparous women with spontaneous and induced labor and multiparous women with spontaneous labor and unscarred uterus, which could be useful information for directing healthcare improvement measures. Both OASIS and PPH rates in Sweden were remarkably high, in line with previous observations, and can probably to some extent be explained by population characteristics and intrapartum factors, for example high birthweight, episiotomy use or management of second stage of labor 20,33–35 . Regardless of cause, a reduction of these outcomes is desirable, preferably without raising CS and OVD rates too high and while maintaining the safety and wellbeing of newborns.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Notably, the largest contributors to the total rates of all outcomes except CS were women with singleton term cephalic pregnancies and unscarred uterus, nulliparous women with spontaneous and induced labor and multiparous women with spontaneous labor and unscarred uterus, which could be useful information for directing healthcare improvement measures. Both OASIS and PPH rates in Sweden were remarkably high, in line with previous observations, and can probably to some extent be explained by population characteristics and intrapartum factors, for example high birthweight, episiotomy use or management of second stage of labor 20,33–35 . Regardless of cause, a reduction of these outcomes is desirable, preferably without raising CS and OVD rates too high and while maintaining the safety and wellbeing of newborns.…”
Section: Discussionsupporting
confidence: 85%
“…31,32 Importantly, the number of adverse events in the specific group depends not only on the risk within the group but also on the size of the groups, therefore high-risk groups were not necessarily the episiotomy use or management of second stage of labor. 20,[33][34][35] Regardless of cause, a reduction of these outcomes is desirable, preferably without raising CS and OVD rates too high and while maintaining the safety and wellbeing of newborns. Intuitively, one is tempted to start this betterment in the groups with the highest rates of the undesirable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Corbett et al 1 for their interest in our article 2 and for their comments about the application of the Ten Group Classification System for perinatal audit. In our analysis, we elected to exclude deliveries classified in Robson groups 6-10 because these accounted for a low proportion of the initial study cohort (n = 158 847; 9.0%).…”
Section: Authors Reply Re: the Ten Group Classification System -First...mentioning
confidence: 99%
“…An observational study using vaginal culture results unavailable until after birth has shown an association between untreated mycoplasma infection and preterm birth. 2 However, to determine whether mycoplasma causes preterm birth and whether treatment prevents it, a randomised trial of treatment or placebo in infected women at elevated risk of preterm birth is needed. This may not be feasible.…”
Section: Re: Genital Mycoplasma Infection and Preterm Birth Outcome: ...mentioning
confidence: 99%
“…Based on observational studies and anecdotal evidence, our practice is to screen women with a history of preterm birth, late miscarriage or short cervix for ureaplasma, mycoplasma and bacterial vaginosis in the second trimester and treat those who are positive. [2][3][4] We also test women with threatened preterm labour remote from term and treat those who are positive, sometimes with marked reduction in symptoms. In keeping with Taylor-Robinson's paper, treatment failures with azithromycin used for Mycoplasma hominis have prompted a switch to clindamycin, whose activity against both mycoplasma and bacterial vaginosis may explain its better performance than metronidazole in the prevention of preterm birth.…”
Section: Re: Genital Mycoplasma Infection and Preterm Birth Outcome: ...mentioning
confidence: 99%